Mixed emotions: binary paths of humble leadership influencing employee behavior - Shen, Yanping; Wu, Wenbing; Xu, Shufei; Wang, Yi; Cai, Fangyuan (Frontiers in Psychology, 2025)
The importance of humble leadership has garnered increasing attention among researchers. Most existing research focuses on its positive effects, but its negative effects are rarely discussed. From a more dialectical perspective, this study found that humble leadership has a dual impact, as it can foster employee innovative behavior and also trigger instances of time theft. Based on social information processing theory, this study used a questionnaire survey and structural equation modeling. Through the data analysis of 303 sample, the results suggest that humble leadership can reduce employee time theft by reducing employees' perceived acceptance of norm violations, while stimulating employee respect can increase employee innovative behavior, as well as supervisor's organizational embodiment can have a positive moderating effect. This study examines the mechanism of the influence of humble leadership on employee innovative behavior and time theft, broadens the body of humble leadership research, reveals the role of supervisor's organizational embodiment, and provides theoretical insights for enterprises to optimize organizational management.